A General and Selective Rhodium‐Catalyzed Reduction of Amides, N‐Acyl Amino Esters, and Dipeptides Using Phenylsilane. Issue 21 (13th April 2016) - Das, Shoubhik; Li, Yuehui; Lu, Liang‐Qiu; Junge, Kathrin; Beller, Matthias
Abstract: This article describes a selective reduction of functionalized amides, including N ‐acyl amino esters and dipeptides, to the corresponding amines using simple [Rh(acac)(cod)]. The catalyst shows excellent chemoselectivity in the presence of different sensitive functional moieties. Abstract : A selective reduction of functionalized amides, including N ‐acyl amino esters and dipeptides, to the corresponding amines using simple [Rh(acac)(cod)] is described (see scheme). The catalyst shows excellent chemoselectivity in the presence of different sensitive functional moieties. Even the selective reduction of a secondary amide bond in the presence of a ketone is possible.